Investigation of acoustic radiation force to clean stone fragments - Lee, Jerico Wei Da (2015)
After Extracorporeal Shockwave Lithotripsy (ESWL) breaks a kidney stone up into fragments small enough to be passively passed through the urine stream, some fragments may be stuck in the lower ends of the kidney. A possible non-invasive method for removing such fragments may be to utilise a medical ultrasound transducer to apply acoustic radiation force and guide the fragments out of the kidney. Acoustic Radiation Force arises from an interaction between an acoustic wave and an obstacle in the propagation path of the wave. This study investigates how the driving acoustic radiation force, as well as other forces such as the Kutta-Joukowski lift that affect the trajectory of the obstacle in the path of an acoustic wave. Through virtual simulation methods by using Matlab and an ultrasound simulator named FOCUS software, the trajectory of a sphere in water acting under the influence of an acoustic field from an ultrasound transducer is measured. Different waveforms and initial conditions are utilised, with the results analysed to attain a better understanding of the suitability of a medical ultrasound transducer as a tool to help remove kidney stone fragments.